Wage Moderation in France - Estevão, Marcello M. (International Monetary Fund, 2002)
Using household level data for France from 1990 to 2000, we estimate a relationship between wages and unemployment taking into account compositional, time and regional effects. We show that this relationship shifted outward during the 1990s most likely because of a structural change in workers'' behavior, i.e. ""wage moderation"". The outward shift was particularly large between 1996 and 2000 and undoubtedly contributed strongly to the exceptional employment performance during that period